Intersection Control Evaluation for Highway Safety Analysis - Mishra, Anuj; Pandeya, Ayush (International Journal on Engineering Technology, 2024)
Road traffic accidents take more lives than a combination of other accidents and natural disasters. An article published on September 9, 2023, in the Nepali Times, reported that between April 2022 and April 2023, a total of 2,320 individuals lost their lives, with 28,856 sustaining injuries, many resulting in lifelong impairment. Traffic studies have revealed that Intersection Control Evaluation (ICE) facilitates strategic decision-making through the use of factual information, data, and metrics. The primary objective of this research on intersection control evaluation is to explore how the screening process and the selection of alternative intersections in ICE contribute to the reduction of accidents at intersections. A focused examination of the literature assessing the methodology’s effectiveness in maintaining intersection safety suggests that intersection control evaluation aids in strategy selection during expansion and signal usage at major intersections. Subsequent discussions utilized various spreadsheet tools and online forums. The findings indicate that ICE serves as an effective framework for screening intersection alternatives and identifying optimal solutions. Results show that tools such as ’Capacity Analysis for Planning of Junctions’ (CAP-X) effectively evaluate intersection types. Additionally, ’Safety Performance of Intersection Control Evaluations’ (SPICE) is employed for safety analysis at grade intersections. Cost analysis, based on results obtained from the Life Cycle Cost Estimation Tool (LCCET) spreadsheet, demonstrated the cost-effectiveness of this approach. In light of the results and discussions, intersection control evaluation should play a crucial role in implementing safer, more balanced, and cost-effective solutions at road intersections.